2003
DOI: 10.1084/jem.20021911
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against Neisseria meningitidis Using Three Variants of the Lipoprotein GNA1870

Abstract: Sepsis and meningitis caused by serogroup B meningococcus are devastating diseases of infants and young adults, which cannot yet be prevented by vaccination. By genome mining, we discovered GNA1870, a new surface-exposed lipoprotein of Neisseria meningitidis that induces high levels of bactericidal antibodies. The antigen is expressed by all strains of N. meningitidis tested. Sequencing of the gene in 71 strains representative of the genetic and geographic diversity of the N. meningitidis population, showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
573
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 382 publications
(590 citation statements)
references
References 40 publications
11
573
1
1
Order By: Relevance
“…However, existing limitations of OMV-based meningococcal vaccines, including lower efficacy in young children (Costa et al, 1996;De Moraes et al, 1992;Sierra et al, 1991;Tappero et al, 1999), inability to induce immunological memory (Wedege et al, 1998) and failure to provide cross-protection against non-vaccine strains, may delay their use (Pollard and Levin, 2000). Alternatively, reverse vaccinology approaches have identified antigens that induce antibactericidal antibody responses against the spectrum of meningococcal serogroup B strains associated with invasive disease (Giuliani et al, 2006;Masignani et al, 2003). These target antigens are being evaluated as candidates for a universal serogroup B subunit vaccine and, if effective, will be an important intervention against this disease in epidemiological situations such as encountered in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…However, existing limitations of OMV-based meningococcal vaccines, including lower efficacy in young children (Costa et al, 1996;De Moraes et al, 1992;Sierra et al, 1991;Tappero et al, 1999), inability to induce immunological memory (Wedege et al, 1998) and failure to provide cross-protection against non-vaccine strains, may delay their use (Pollard and Levin, 2000). Alternatively, reverse vaccinology approaches have identified antigens that induce antibactericidal antibody responses against the spectrum of meningococcal serogroup B strains associated with invasive disease (Giuliani et al, 2006;Masignani et al, 2003). These target antigens are being evaluated as candidates for a universal serogroup B subunit vaccine and, if effective, will be an important intervention against this disease in epidemiological situations such as encountered in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…fHbp plays a prominent role in meningococcal pathogenesis by recruiting human factor H (hfH) to the bacterial surface, thus protecting the bacterium from complement-mediated killing (10)(11)(12). fHbp is expressed by the majority of virulent meningococcal strains; its sequence displays extensive variability, allowing classification into three main variant groups (var1, -2, and -3) or two subfamilies (A and B) sharing limited cross-protection (13).…”
mentioning
confidence: 99%
“…fHBP protein sequences are conserved and segregate into two distinct subfamiles, A and B 3,4 or three variants. 5 Previous work demonstrated that a vaccine containing one fHBP from both subfamily A and B induces functional immune responses in mice, rabbits, macaques and humans capable of killing a diverse population of invasive serogroup B isolates and that the level of fHBP expressed by isolates is indicative of whether the strain can be killed in an in vitro SBA. 3,6,7,12 The results presented here show that fhbp is also present in all serogroup C clinical isolates that have caused invasive disease in the US in 2000-2001.…”
Section: Methodsmentioning
confidence: 99%
“…The fhbp gene is present in all serogroup B meningococcal isolates examined to date and, based on sequence variation, can be divided into two distinct subfamilies, A and B, 3,4 based on one classification system or three variants, 1, 2 and 3, based on a separate system. 5 A bivalent fHBP vaccine containing a member of each subfamily has been shown to elicit broad bactericidal activity against serogroup B isolates expressing heterologous fHBP 6 and is currently in clinical studies as a vaccine against serogroup B disease. 7 Limited sequence data suggests that the fhbp gene is also present in other N. meningitidis serogroups.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%